GELOMBANG PENETRASI IFRS TERHADAP DOMINASI US GAAP: ADAKAH PERBEDAAN MENDASAR BASIS LANDASAN KONSEPTUAL? - Sururi . (Akademi Akuntansi YKPN Yogyakarta, 2009)
Since 1973, IASC has been introduced the International Accounting Standards (IAS), as part of its endeavor to horminize financial reporting internationally. However, it seems that until the year 2000s, the IAS had not been widely accepted, even though the founders of IASC deeply belive that the world very need the standard, sooner or later, it is due to the fact that from day to day the business world becoming more and more boarderless, MNC is the fact that could not be stopped, therefore worldwide comparability of the financial statements no longer a need, but it is a must. Started on 2001, after the body changed its name become IASB and the standard changed its name become IFRS, suddenly the standard becoming more and more widely accepted, a number of accounting academician and practitioner shaky facing the penetration of the IFRS wave, it is due to the lack of understanding of IFRS, particularly for those who settle already with US GAAP. This article is aimed to analyze and introduce the conceptual framework and principles underlying the standard either for US GAAP or for IFRS.Keywords: IAS, harmonize financial reporting internationally, comparability, IFRS, US GAAP